Construction of a Linkage Map and QTL analysis for Black Rot Resistance in Brassica oleracea L. (International Journal of Natural Sciences, 2011)
For quantitative trait loci (QTL) controlling resistance to Xanthomonas campestris pv. Campestris, we constructed linkage map using cleaved amplified plymorphic sequences (CAPS) and sequence-related amplified polymorphism (SRAP) analysis with disease rating of F3 families obtained from a susceptible broccoli and resistant cabbage [Green commet P09 × Reiho P01]. We established inoculation technique. In this technique, leaves from approximately 50-day old F3 plants were inoculated by cutting 1.0 cm at mid vain near the margins. A total of 38 CAPS and 60 SRAP primer pairs were screened to assess parental polymorphism against black rot resistance. Ninety two markers were distributed in 10 linkage groups (LGs) covering 320.5 cM (centimorgan), with average 3.56 cM interval between markers. Two genomic regions on LG 2 and LG 9 were significantly associated with resistance to the disease. The analysis revealed QTLs in the map interval between CAM1 – GSA1 on LG 2 accounting for up to 10% of the phenotypic variation and one QTL in the map interval between F12-R12e – BORED on LG 9 explaining 16% phenotypic variation with LOD score of 3.09. Two additional non-significant QTLs on LG 3 in the interval between CHI – ASB1 (LOD = 2.04) and on LG 7 in the interval between IPI – FLC3 (LOD = 2.25) were also detected for resistance to the disease. The QTLs, which were mapped to LG 2 and LG 9 for the disease, could be useful for marker-assisted selection in resistance breeding. Key words: Linkage map; QTL; Black rot; Resistance; Brassica oleracea  DOI: http://dx.doi.org/10.3329/ijns.v1i1.8591 International Journal of Natural Sciences (2011), 1(1):1-6